Results of a cognitive behavior therapy-based intervention for antenatal anxiety on birth outcomes in Pakistan: a randomized control trial - Siebach, Kirsten F.; Perin, Jamie; Malik, Abid; Atif, Najia; Zaidi, Ahmed; Rahman, Atif; Surkan, Pamela J. (Scientific reports, 2024)
Antenatal anxiety is among the risk factors for adverse birth outcomes, which are common in Pakistan. Between 2019 and 2022, we conducted a randomized controlled trial to evaluate the effects of the Happy Mother-Healthy Baby program, designed to reduce anxiety during pregnancy through use of Cognitive Behavior Therapy, on birth outcomes with 796 women in Rwalpindi, Pakistan. We performed intent-to-treat analysis and per protocol analyses. Intention-to-treat analyses showed no difference in the odds of low birthweight (LBW) (Adj. OR = 0.82, 95% CI 0.55–1.28 p = 0.37), preterm birth (PTB) (Adj. OR = 1.20 95% CI 0.83–1.71, p = 0.33) or small-for-gestational age (SGA) birth, (Adj. OR = 0.76, 95% CI 0.56–1.09, p = 0.16). Among completers who received ≥ 5 intervention sessions, the odds of LBW and SGA were 39% and 32% lower (Adj. OR = 0.61, 95% CI 0.43–0.87, p < 0.01; Adj. OR = 0.68, 95% CI 0.53–0.89, p < 0.01). The significant LBW and SGA results among the intervention completers suggest that the program may be effective when a sufficient dose is received. However, confirmation of these findings is needed due to the fact that randomization is not maintained in completer analyses. Clinical Trial Registration: ClinicalTrials.gov Identifier: NCT03880032, 19/03/2019.